Gendering the Islamic Judiciary: Female Judges in the Religious Courts of Indonesia - Nurlaelawati, Euis; Salim, Arskal (Al-Jamiah: Journal of Islamic Studies, 2013)
Compared to other Muslim countries, Indonesia has been the forefront, if not the frontrunner, in welcoming women to occupy a position as judges at the Islamic court. Despite few Indonesian women were already sitting at Islamic courtrooms and hearing cases on family law issues as early as in 1960s, it was only in 1989 that Indonesia fully accommodated female judges at the religious courts. From this onwards, female judges were recruited more than ever and began accessing a number of rights and positions like their male counterparts. This paper discusses female judge and women litigants at Islamic courts of Indonesia. This paper not only discusses the way in which women were recruited to be judges at the Indonesian Islamic courts, but also explores some factors leading Indonesian women to engage in the judicial practice. In addition, this paper looks at the way in which female judges exercise their authority to protect rights of disadvantaged women litigants. This paper argues that despite female judges have the same skills in interpreting law as their male colleagues do and that they have to some extent better gender sensitivity, they unfortunately have not maximised utilising these legal skills for the benefits of women litigants.[Dibandingkan dengan negara-negara Islam lainnya, Indonesia telah menjadi garda depan âjika tidak disebut peloporâ dalam mengangkat perempuan sebagai hakim di Pengadilan Agama. Meski pada decade 1960-an sejumlah perempuan sudah menduduki jabatan hakim dan telah menyidangkan kasus-kasus keluarga di Pengadilan Agama, hanya pada tahun 1989 pengangkatan perempuan pada Pengadilan Agama ditegaskan secara formal dan legaal oleh pemerintah Indonesia. Sejak saat itu, jumlah hakim perempuan di pengadilan agama meningkat dan mereka memiliki kesemepatan untuk memperoleh hak dan posisi penting di Pengadilan Agama, sejajar dengan hakim laki-laki. Artikel ini mendiskusikan keterlibatan perempuan, baik sebagai hakim maupun pihak yang berperkara, di Pengadilan Agama. Tidak hanya menjelaskan bagaimana perempuan direkrut sebagai hakim di Pengadilan Agama, artikel ini juga mengulas faktor-faktor penting yang mendorong keterlibatan perempuan dalam praktek peradilan. Selain itu, juga dijelaskan peran hakim perempuan dalam melindungi hak para perempuan yang berperkara di pengadilan. Penulis berkesimpulan bahwa meski para hakim perempuan memiliki kompetensi yang sama dalam memutus perkara seperti para hakim laki-laki dan dalam batas tertentu memiliki sensitifitas gender yang lebih kuat ketimbang laki-laki, peran mereka masih terlihat belum maksimal, terutama dalam memberikan perlindungan terhadap pemenuhan hak-hak perempuan.]